PENGARUH KEPEMILIKAN MANAJERIAL, KEPEMILIKAN INSTITUSIONAL, DAN KEPEMILIKAN ASING TERHADAP PRAKTIK PENGUNGKAPAN SUSTAINABILITY REPORT - Adimulya Nurrahman; Sudarno Sudarno (Diponegoro Journal of Accounting, 2013)
This study aims to empirically analyze the effect of ownership in a company that consists of managerial ownership (MANJ), institutional ownership (INST), and foreign ownership (FOREIGN) the disclosure practices of corporate sustainability report. Sustainability Report (SR) is the dependent variable in this study were measured by a dummy variable that consists of companies that disclose and not disclose SR. The independent variables were studied including the percentage of managerial ownership, the percentage of institutional Ownership and Foreign Ownership percentages. This study also uses the control variables, the size of the company. Data from this study were obtained from the financial statements and annual report of manufacturing firms drawn from the Indonesia Stock Exchange. The population in this study are all companies listed in the Indonesia Stock Exchange (BEI), with the exception of companies - companies that are included in the category of banking, credit agencies other than banks, securities and insurance during the period from 2007 to 2011 as many as 98 companies that do not express SR and 98 companies that expressed SR. Sampling method contol case. The type of data used are secondary data in the form of annual reports by the media companies. Data analysis tools used were Multivariate Analysis wait SPSS computer program. The results of this study indicate that institutional ownership (INST) and foreign ownership (FOREIGN) positive effect on disclosure of corporate sustainability report, but managerial ownership (MANJ) had no effect on the disclosure of corporate sustainability report.